Kedudukan Alat Bukti Elektronik sebagai Jenis Alat Bukti yang Sah dalam Kitab Undang-Undang Hukum Acara Pidana Tahun 2025 - Muhammad Rusydan Annas (Jurnal Hukum dan Sosial Politik, 2026)
The rapid development of information technology has necessitated reforms in Indonesia's criminal procedural law to accommodate advances in digital technology. This study aims to analyze the legal status of electronic evidence as admissible evidence under Law Number 20 of 2025 concerning the Indonesian Code of Criminal Procedure and to examine its implications for the criminal evidentiary system. The research employs a normative legal method using statutory and conceptual approaches through the analysis of legislation, legal doctrines, and relevant literature. The findings indicate that electronic evidence has been formally recognized as an independent form of admissible evidence within Indonesia's criminal justice system. This legal recognition provides greater legal certainty regarding the use of electronic evidence, enhances the effectiveness of the evidentiary process, and supports a law enforcement system that is more adaptive to developments in information technology. Nevertheless, the recognition and application of electronic evidence must continue to uphold the principle of due process of law to ensure the protection of the rights of all parties involved and to guarantee that criminal proceedings are conducted fairly, proportionally, and in accordance with the applicable legal provisions.